The nexus between corporate governance, asset structure, and value of listed firms: evidence from Kenya - Barine Nkonge Habakkuk; Kariuki Samuel Nduati; Kariuki Peter Wang’ombe (Investment Management & Financial Innovations, 2023)
Shareholders of listed firms are guaranteed reasonable security prices due to enhanced firm value, which translates to global wealth creation. However, firms’ value has declined globally. Therefore, this paper uses a causal-comparative design and panel data regression model to explore the nexus between corporate governance, asset structure, and value of Kenyan-listed firms from 2010 to 2019. Secondary data were extricated from audited financial reports of 51 firms. As hypothesized, the results show a positive relationship between board composition and firm value with a regression coefficient (0.17, p < .05). The composition of the audit committee is positively associated with firm value with a regression coefficient of (0.629, p < .05). A tangible and notable correlation exists between protecting shareholders’ rights and firm value with a regression coefficient of (0.28, p < .05), while financial disclosure was significant with a regression coefficient of (1.15, p < .05). Plant, property and equipment positively and significantly affect firm value with a regression coefficient of (2.10, p < .05), while financial assets had (0.28, p < .05), which was significant. Current assets positively and significantly affect firm value with a regression coefficient of (1.87, p < .05). Finally, the results reveal a positive but insignificant correlation between firm size and value with a regression coefficient of (0.22, p < .05), while the relationship between firm age and value is negative but insignificant with a regression coefficient of (–0.003, p < .05). The study recommends that sufficient managerial effort be directed towards corporate governance and asset structure to maximize shareholder value.